2017
DOI: 10.1097/wnf.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Oral Somatic Delusions Ameliorated With Brain Perfusion Asymmetry: A Case Report

Abstract: BackgroundOral cenesthopathy is the complaint of abnormal oral sensation where no underlying organic cause can be identified. It is also called oral dysesthesia or oral somatic delusion and classified as delusional disorder, somatic type. The patients with oral cenesthopathy show right > left asymmetric regional cerebral blood flow (rCBF) in the broad brain region. However, the studies scrutinizing the rCBF change before and after the successful treatment are still a few so far.CaseWe present 2 cases of oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Under the clinical entity of DDST, some case reports and reviews suggested that antidepressants, antipsychotic drugs, and electroconvulsive therapy (ECT) are effective. When only the oral symptoms are present, paroxetine, 12 fluvoxamine, 13 amitriptyline, 13 , 14 sulpiride, 14 risperidone, 13 , 15 olanzapine, 13 perospirone, 11 aripiprazole, 16 and ECT 11 , 26 were reported to be effective. In this study, aripiprazole was the most effective medicine, especially in low doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the clinical entity of DDST, some case reports and reviews suggested that antidepressants, antipsychotic drugs, and electroconvulsive therapy (ECT) are effective. When only the oral symptoms are present, paroxetine, 12 fluvoxamine, 13 amitriptyline, 13 , 14 sulpiride, 14 risperidone, 13 , 15 olanzapine, 13 perospirone, 11 aripiprazole, 16 and ECT 11 , 26 were reported to be effective. In this study, aripiprazole was the most effective medicine, especially in low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapy and pharmacotherapy are the mainstream treatments for oral cenesthopathy. Antidepressants and antipsychotic drugs were prescribed in our clinic depending on the patients’ symptoms, medical complications, former reports, 11 16 personality features, and background such as lifestyle, habits, income, opportunity, and family relationships. If dental treatment was needed during our treatment, their family dentists or attending dentists in our clinic (YU, AM, YS, LM, SS, KK, TT, TW, TS, MW, MT, and TY) treated them while confirming their symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…These delusions cause enormous anguish, and sometimes lead to suicide [ 2 ]. Psychotropics such as antipsychotics [ 2 4 ] and antidepressants [ 5 , 6 ] are efficacious for some patients. For pharmacotherapy-resistant cases in DDST [ 7 ], bipolar disorder [ 8 ], and schizophrenia [ 9 ], electroconvulsive therapy (ECT) has been reported to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…The CNS involvement were suggested in previously. In a case report with OC, the asymmetric CBF pattern ameliorated after the treatment with aripiprazole [22]. The case report of the modi ed electroconvulsive therapy to the OC patients showed improved CBF asymmetry in the temporal region and reduced the symptoms of OC [23].…”
Section: Discussionmentioning
confidence: 94%